Basic engineering mathematics - Bird, John (Routledge, 2014)
"John Bird's approach to mathematics, based on numerous worked examples and interactive problems, is ideal for vocational students who require an entry-level textbook.Theory is kept to a minimum, with the emphasis firmly placed on problem-solving skills, making this a thoroughly practical introduction to the basic mathematics engineering that students need to master. The extensive and thorough topic coverage makes this an ideal introductory textbook for vocational engineering courses, including the BTEC National Specifications. Now in its sixth edition, Basic Engineering Mathematics has helped thousands of students to succeed in their exams. The new edition includes a section at the start of each chapter to explain why the content is important and how it relates to real life. It is also supported by a fully updated companion website with resources for both students and lecturers. The text contains over 750 worked problems and it has full solutions to all 1600 further questions contained in the 161 practice exercises. All 420 illustrations used in the text can be downloaded for use in the classroom"--